Potential effects of SARS-CoV-2 on the gastrointestinal tract and liver - Han-Yu Lei (Biomedicine & Pharmacotherapy, 2021)
COVID-19 is a pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Early reported symptoms include fever, cough, and respiratory symptoms. There were few reports of digestive symptoms. However, with COVID-19 spreading worldwide, symptoms such as vomiting, diarrhoea, and abdominal pain have gained increasing attention. Research has found that angiotensin-converting enzyme 2 (ACE2), the SARS-CoV-2 receptor, is strongly expressed in the gastrointestinal tract and liver. Whether theoretically or clinically, many studies have suggested a close connection between COVID-19 and the digestive system. In this review, we summarize the digestive symptoms reported in existing research, discuss the impact of SARS-CoV-2 on the gastrointestinal tract and liver, and determine the possible mechanisms and aetiology, such as cytokine storm. In-depth exploration of the relationship between COVID-19 and the digestive system is urgently needed.